Psycholinguistics Angle of Interaction Model Using Classical Music in ESL Reading - Herda, Rozanah Katrina; Kozuka, Yoshitaka (TLEMC (Teaching and Learning English in Multicultural Contexts), 2024)
When introduced into English as a Second Language (ESL) reading classrooms, it has the potential to assist students in becoming more immersed in the language. The complex melodies and emotionally charged compositions characteristic of classical music have the potential to produce an atmosphere better suited to the comprehension of language in ESL reading classrooms. This mixed-method study that involved 33 students from one university in Indonesia was aimed to (1) investigate the significant difference between the mean scores of the pretest and the posttest in ESL reading using classical music and (2) describe the students' reflections on using classical music in the reading classroom. This study used pretest-posttest and students' reflection sheets as data collection instruments. The pretest and posttest results indicated that classical music significantly improved students' reading skills in ESL classrooms. The written reflections showed students were highly motivated to join the reading activity, as classical music was beneficial for enhancing students' mood and concentration, affecting their comprehension, vocabulary collection, and cognitive skills.Keywords: learning experiences, classical music, ESL reading, psycholinguistics